It's Sharing Day! - Larsen, Kirsten; Zalme, Ron. (New York : Simon Spotlight/Nick Jr., 2007)
Dora goes to her grandmother's house to celebrate Sharing Day.
Text mainly in English with some Spanish words.
"Based on the TV series Dora the Explorer as seen on Nick Jr."--T.p. verso.
1 13 30 31
Keywords: Dora the Explorer (Fictitious character) -- Juvenile fiction; Sharing -- Juvenile fiction; Grandmothers -- Juvenile fiction; Animals -- Juvenile fiction; Explorers -- Juvenile fiction